The Anglo-Norman Vegetius: a thirteenth century translation of the "De re militari" - Carley, Lionel Kenneth (1962)
The thesis is divided into three main sections i) Introduction ii) Text iii) Critical Notes and Glossary. The frontispiece shows the title page of the Anglo-Norman MS translation of Vegetius' De re militari. i) Introduction: In the opening two chapters, the historical setting of the translation is examined. First, the background to the writing in the fourth century of the original Latin text is established, and an outline is given of the substance of the text; then a study is made of the Vegetian tradition in France from the later years of the thirteenth century to the present day. The manuscript, its date and its authorship are discussed in Chapters 3 and 4. Then the value of the French text as a translation is discussed. The sixth and longest chapter examines the language of the translation, noting points of divergence from Continental French which generally fit into the pattern of Anglo-Norman usage. A short chapter is given over to outlining the plan followed in establishing the text of this edition. The Notes to the Introduction conclude this part of the thesis. ii) Text: The text is basically that of Add.MS.1. of the Marlay Collection of the Fizwilliam Museum, Cambridge. This is a unique manuscript. Corrections and emendations, which have been kept to a bare minimum, are shown in the footnotes. iii) Critical Notes and Glossary The Critical Notes are designed to amplify and clarify the text. Extensive reference is made to the Latin original, and many difficult or obscure passages are translated into English. The Notes are followed by a Select Glossary and an Index of Proper Names. Two appendices list the various manuscripts of the mediaeval French translations of Vegetius, together with certain additional Latin manuscripts of the De re militari. The volume ends with a list of the principal works consulted in the preparation of this thesis.